Sexual Violence in Higher Education Institutions: Obstacles and Strategies in Creating Safe and Comfortable Campuses - Attala, Dendi Rafif; Nurhaeni, Ismi Dwi Astuti (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2024)
Sexual violence on campus is a serious problem that requires immediate attention and action. This research aims to identify and explore implementation barriers and strategies for higher education institutions (HEIs) to create safe and comfortable campuses free from sexual violence. This research is qualitative-descriptive, with multiple study sites in Central Java and Special Region Yogyakarta, i.e., Universitas Sebelas Maret (UNS), Universitas Pembangunan Nasional Veteran Yogyakarta (UPN Veteran Yogyakarta), Universitas Negeri Yogyakarta (UNY), Institut Seni Indonesia Surakarta (ISI Surakarta), and Universitas Islam Negeri Walisongo Semarang (UIN Walisongo). The results indicate the main obstacles of HEIs in creating safe and comfortable campuses free of sexual violence are inadequate and not gender responsive in preventing and handling sexual violence. The HEIs need to build a more robust and comprehensive foundation to create a space that is free from sexual violence and supports the welfare of all academic community members. The findings suggest that the strategies to be developed are embedding the issue in the learning process, strengthening governance, and building community networks and collaborative partnerships.